A Young Boy with Brittle Hair - Nassim Tootoonchi; Vahideh Azhari; Zahra Razavi; Shadab Seraji; Nika Kianfar; Hamidreza Mahmoudi; Maryam Daneshpazooh (Karger Publishers, 2022)
Trichothiodystrophy (TTD) is a rare multisystem disorder with an autosomal recessive mode of inheritance. TTD presentations vary from only hair abnormalities like brittle, fragile hair to physical and mental retardation. Mutations of DNA repair genes have been identified as responsible for the disease. A 5-year-old boy presented with sparse, short, and brittle hair to our clinic. He was born to consanguineous parents. Trichoscopy and light microscopy revealed broken hairs with no specific shaft defect. Due to the inaccessibility of the polarized microscopy, a bedside technique was employed. We used a polarized dermatoscope and a mirror in order of achieving transillumination of the hair shafts, which revealed striking bright and dark bands. These bands are referred to as "tiger tail," which is the pathognomonic sign of TTD. Subsequent polarizing microscopy also confirmed the clinical diagnosis. This highlighted a feasible method for observing the tiger tail, which expanded the known clinical diagnostic tools of TTD.